2009
DOI: 10.1016/s0034-7094(09)70078-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Epidural Analgesia and Continuous Lumbar Plexus Block on Functional Rehabilitation after Total Hip Arthroplasty

Abstract: The greater effectivity of epidural analgesia did not translate in improvement of the rehabilitation process nor did it decrease the time necessary to achieve end goals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 25 publications
0
11
1
1
Order By: Relevance
“…However, these results also differ from other studies. Duarte et al 3 have reported that patient The incidence of complications for both groups is shown in table 2. cLPB group had a total number of complications significantly lower as compared to the epidural group (4.7% cLPB versus 23.4% epidural). However, the scarce incidence of each complication does not allow establishing statistically significant differences between groups.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…However, these results also differ from other studies. Duarte et al 3 have reported that patient The incidence of complications for both groups is shown in table 2. cLPB group had a total number of complications significantly lower as compared to the epidural group (4.7% cLPB versus 23.4% epidural). However, the scarce incidence of each complication does not allow establishing statistically significant differences between groups.…”
Section: Discussionmentioning
confidence: 92%
“…Unfortunately, the low incidence of secondary effects and complications in the sample does not allow inferring the existence of significant differences between cLPB and epidural techniques. cLPB seldom has severe complications being known intoxication by local anesthetics following inadvertent intravascular injections, spinal administration, intraperitoneal puncture, subcapsular renal hematoma by renal perforation and retroperitoneal hematoma 1,3,5 . Drug dispersion to the epidural space was considered by other authors as the most frequent LPB complication, with incidence of 5% 4,5,10 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations